Effect of the use of different types and dosages of mineral additions on the bond strength of lap-spliced bars in self-compacting concrete - Turk, Kazim; Karatas, Mehmet; Ulucan, Zulfu C. (Springer, 2010)
In this study, nine different types of concrete were adopted: normal concrete (NC) with low slump (68 mm) and eight types of self-compacting concrete (SCC) in which cement was partially replaced by four kinds of replacements (25%, 30%, 35% and 40%) of class F fly ash (FA) and by four kinds of replacements (5%, 10%, 15% and 20%) of silica fume (SF). The main objective of this research was to evaluate the effect of different types and dosages of mineral additions on the moment capacities and stiffnesses of the beam specimens and the bond strength of tension lap-spliced bars embedded in NC and self-compacting concretes (SCCs). To achieve these objectives, 27 full-scale beam specimens (2000 x 300 x 200 mm) were tested. In all beam specimens, 20 mm reinforcing bars were used with a 300 mm splice length as tension reinforcement. The variable used was the amount of FA and SF incorporated into SCC. Each beam was designed with bars spliced in a constant moment region at midspan. The splice length was selected so that bars would fail in bond, splitting the concrete cover in the splice region, before reaching the yield point. Moreover, bond strength of SCC beams was compared to that of NC beams of the same dimensions, steel configuration and approximately the same water-to-cement ratio. In conclusion, the beam specimens produced from SCC containing 5% SF and 30% FA had the highest normalized bond strength with 1.07 whilst the replacements of Portland cement (PC) by an equal weight of FA or SF in SCC had generally the positive effect on the bond strength of reinforcing bar regardless of the dosage of mineral admixture compared to the specimen with NC indicating that SCC due to its superior filling capability more effectively covered the reinforcements and the grain-size distribution and particle packing improved ensuring greater cohesiveness. Moreover, the beam specimens produced from SCC with SF had the greatest stiffness compared to other all beams as result of the improvement of concrete pore structure due to the pozzolanic activity and the filler effect of high fineness silica fume.
Keywords: Bond strength; Full-scale beam; Lap-spliced bar; Mineral addition; Self-compacting concrete